Effects of Shot Peening on Fatigue Life of Ground Component of 7075-T6 Aluminum Alloy. Issue 1 (January 2020) - Cheng, Xiuquan; Zhang, Junhao; Sheng, Xiangfei; Xia, Qinxiang
Abstract: The aircraft corroded components can continue to be used after removing the corroded portion by grinding and strengthening the ground area by shot peening. The finite element analysis model of the ground specimen with complex shape surface was established based on ABAQUS software. The residual stress distributions under three conditions of without shot peening, ground surface shot peening and three surfaces shot peening were analysed. On this basis, the cyclic alternating load was introduced into the shot peening model, and the fatigue analysis was carried out based on MSC. Fatigue software. The result shows that the position of the maximum tensile stress moves from the surface to the subsurface of the ground specimen after shot peening; shot peening conditions will affect the location of the crack sources, the propagation direction of the crack; with the increasing of the numbers of peened surface, the location of stress danger point shifts from ground surface to side surface or sub-surface, and the crack propagation velocity decreases. All of these increases the fatigue life. The experimental results conform well to the simulation one.